The Effect of High- and Low-Frequency Repetitive Transcranial Magnetic Stimulation Therapy on Serum Brain-Derived Neurotropic Factor Level and Motor Ability in Ischemic Stroke Patients: A Single-Center Study - Bintang, Andi Kurnia; Akbar, Muhammad; Amran, Muhammad Yunus; Hammado, Nurussyariah (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Repetitive transcranial magnetic stimulation (rTMS) is widely used in various neurological cases. rTMS is an effective method of restoration in patients with disability due to central nervous system disorder. AIM: This study aimed to determine the effect of high and low frequency of rTMS on serum brain-derived neurotropic factor (BDNF) levels and motoric abilities in ischemic stroke patients. METHODS: The study design was an experiment with a purposive sampling consecutive on 27 samples with the onset of ischemic stroke 6 months. The study was conducted from February to October 2018; samples were recruited from Neurology Ward of Wahidin Sudirohusodo hospital and its affiliating centers. The serial of rTMS intervention was delivered in “Brain” Clinic center. After fulfilling the inclusion criteria and the initial examination of serum BDNF and motor ability, samples were randomly divided into two groups, intervention group who received standard therapy with rTMS therapy (n = 14) and the control group who only received standard therapy (n = 13). rTMS was given for 2 min frequency of 1 Hertz (Hz) contralesion and 5 Hz ipsilesion every day for 10 days. Assessment of serum BDNF levels and motor skills was conducted on days 1 and 10 of the study. Serum BDNF levels were measured by the monoclonal antibody ELISA technique while motor skills were measured based on the score of the Stroke Rehabilitation Assessment of Movement (STREAM). Serum BDNF values and the STREAM delta score were compared between the two groups of samples. RESULTS: The results showed significant changes only occurred in motor abilities in both groups of samples after 10 days of rTMS therapy with the Wilcoxon test (p < 0.5). The Mann–Whitney U-test showed a more significant change (p < 0.5) in the treatment group than in the control (p = 0.5). CONCLUSION: rTMS has an effect on improving motor ability in ischemic stroke patients. This change in motor abilities is not related to serum BDNF levels in this study.